The Approaches to Deworming of Children - Yu.V. Marushko; Yu.I. Todyka; N.А. Zelena; O.Yu. Stepanyshchenko (Zaslavsky O.Yu., 2016)
The urgency of the problem of the treatment of parasitosis is not in doubt. The World Health Organization has included the control of soil-transmitted helminthiasis into the Global strategy of development. Our study of world literature has confirmed the significant prevalence of helminthiasis and their negative impact on the health and development of children. The aim of our study was to determine the effectiveness of an integrated approach to deworming of children from 3 years using albendazole preparations and sorbent. Deworming with albendazole has been effective, and the addition of sorbent to the therapy contributed to a rapid decrease in the manifestations of helminthiasis.